Objects Tracking Utilizing Square Grid Rfid Reader Antenna Network - Tan, K. G.; Wasif, A. R.; Tan, C. P. (VSP BV, 2008)
Recent trend have shown the, wide spread of RFID application in various areas in line with the realization of low cost RFID tags and increasing worldwide commonality and compatibility. One of the important RFID applications is in object tracking and positioning due to its ability of high speed contactless identification in non-line of sight (NLOS) shared medium. This paper proposes a highly accurate square grid based RFID positioning and tracking technique mainly for use in indoor. It involves design of square grid RFID reader antenna network and position calculation using diffusion algorithm. Square grid reader antenna network presents the solution of placement pattern of RFID reader antennas, hence optimal number of required RFID reader antennas and coverage can be achieved. Diffusion algorithm is a means of exchanging information over short range in estimating RFID tag position by using distance information between reader and tag. The proposed square grid tracking and positioning method is evaluated and compared with the existing positioning method such as Wi-Fi based positioning method and BlueBoT system. The obtained results indicate that the proposed method can achieve average positioning error below 1 m and in some cases error as low as 0.3 m can be reached.